Políticas do espaço: trajetórias identitárias em "Geographies of home"; "Breath, eyes, memory" e "The Agüero sisters" - Juliana Borges Oliveira de Morais (2014)
The novels Breath, Eyes, Memory (1994), written by Edwidge Danticat; The Agüero Sisters (1997), by Cristina García, and Geographies of Home (1999), by Loida Maritza Pérez, published in the same decade by contemporary women writers of the diaspora, privilege female characters and contexts of diaspora and rediasporization. In all three literary works, characters move from Caribbean countries Haiti, Cuba and the Dominican Republic, respectively to the Unites States and undergo identity negotiations which are closely related to the spaces traversed by them. From a comparative perspective, I explore the women characters trajectories in various spaces, focusing primarily on three axes, divided into the chapters that make up this dissertation: space and diaspora, space and gender; and memory spaces. The identity negotiations of the analysed characters point to multiple identifications which are dependent on specific contexts being, therefore, mobile instead of fixed or essential. The characters experiences in the various analysed spaces challenge simplistic binary epistemologies, such as inside/outside and home/ not home, suggesting other forms of conceiving space. With the aim to provide a contemporary reading of the three narratives, I base my analysis on contemporary studies on space and diaspora (especially the Caribbean one) and also on theories concerning identity processes (which emphasize migratory movements), with a focus on feminist literary criticism.